Some issues of improvement of legislative regulation of scientific and expert support of the parliamentary activity of Uzbekistan - Dmitriy Rakhmanov (The American Journal of Political Science Law and Criminology, 2025)
The article undertakes a thorough analysis of the challenges associated with the legislative framework for scientific and expert support within the parliamentary activities of the Republic of Uzbekistan. It is important to acknowledge that, despite the measures that have been implemented, the interaction between parliament and the scientific community requires further development. The necessity of strengthening scientific and expert support of parliamentary activity in the context of modern reforms is emphasized. The article puts forth a series of recommendations to enhance the legislation, including the formation of scientific and expert councils within the chambers of the Oliy Majlis and the elucidation of the process for obtaining feedback from scientific institutions on draft legislation. The implementation of these proposals is expected to enhance the quality of the lawmaking process and the effectiveness of parliamentary control, thereby fortifying the role of the Parliament of Uzbekistan in democratic transformations.